Overview of the research gaps in the rainfall simulator study - Robberta Renuka, Lazarus; Wan Zurina, Wan Jaafar; Ubagaram Johnson, Alengaram; Lai, Sai Hin (Soil Science Society of America, 2023)
Urban flooding, soil erosion, and water pollution are common issues nowadays. The hydrological cycle is being disrupted due to improper planning of development that necessitates extensive studies conducted globally to study ways to address these issues. Significant and accurate data are required to rectify and amend the current situation. Rainfall simulators (RSs) are widely applied in research as they replicate the natural rainfall under controlled conditions and are repeatable. However, based on the published research, it is found that there are significant gaps. The RS has no standardization to cater different environmental conditions, yet vital rainfall characteristics and aspects have to be carried out wisely for better accuracy and data analysis. This review article discusses the gaps and parameters required in RS experiments.